Using Comics to Teach the Human Digestive System: Its Effect on Student Learning Outcomes during a Pandemic - Rita Ria Diana Malau; Silvia Hanna Kusuma Sirait; Jeni Jeni; Insar Damopolii (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2021)
Background: Since COVID-19 learning has been limited and shifted to online learning. Teacher creativity in learning is needed to strengthen student learning outcomes. This study aims to investigate the effect of using comics on student learning outcomes on the material of the human digestive system. Methods: A quasi-experimental research was used on forty-two junior high school students who were randomly selected. Multiple choice tests are used to obtain student learning outcomes. Free sample t-test was used to compare student learning outcomes in comic and non-comic classes. Results: The findings revealed that the average student learning outcomes were better when they were taught using comics than non-comics (p = 0.000 < 0.05). Conclusion: Based on the results of the study, it can be concluded that learning with the application of comic media in science subjects on the human digestive system material has an influence on learning outcomes, with the difference in student learning outcomes in the experimental class being higher than in the control class. Keywords : Comic, Science Learning, Pandemic, Human Digestive System